Bypass grafting operations using conventional technique with off-pump coronary artery bypass grafting in two identical groups conducted at the Penang Hospital (1999-2000) - Kasinathan, Vasantha (2001)
This is a prospective study conducted at the Department of Cardiothoracic Surgery, Penang Hospital, Penang, with a total of one hundred patients were studied over a period of one year between January 1999 to January 2000. Fifty patients who had undergone coronary artery bypass surgery off-pump (OPCAB) were compared with fifty patients who had undergone coronary artery bypass surgery on the heart-lung machine (CPB). Patients who had associated problems of renal failure, stroke, bronchial asthma and recent myocardial infarction were included in the off-pump CABG surgery. The symptoms did not differ in both the groups. They had experienced angina, decreased effort tolerance, palpitations, with NYHA class IT, ill and IV. The predisposing factors of diabetes mellitus, hypertension, hyperlipidemia, smoking, previous family history of heart disease were studied in both these groups. The same pre-operative investigations were performed in both groups of patients. Chest x-ray, ECG, echocardiography, femoral angiogram were done for these one hundred patients. The intra-and post operative bleeding, pre and post operative renal status, echocardiogram, ECG and chest X-rays were compared. The cost effectiveness of both the OPCAB and CPB procedures were reviewed. There was, generally, a better outcome in patients who had undergone a coronary bypass by the offpump (OPCAB) method as when compared to those by the CPB method. This indicates that more cases can be done by the OPCAB method in the future.